Application of cohesive crack model to simulation of rocks mechanical behavior in grain-based distinct element model - Hadi Fathipour-Azar; Seyed Mohammad Esameil Jalali; Seyed Rahman Torabi (International Journal of Mining and Geo-Engineering, 2020)
This paper aims to study the mechanical behavior of rocks subjected to different mechanical loading conditions using the Cohesive Crack Model (CCM) and Grain-Based Model (GBM) in the Distinct Element Method (DEM) simulations. In the GBM-DEM, the Voronoi tessellation scheme is used, and intact materials are simulated as a collection of structural units (particles/blocks) bonded together at their contact areas. Implementing the CCM revealed a nonlinear behavior of grain interfaces under various loading modes. Numerical simulation of a tension-compression and direct shear test was conducted to verify that the CCM was implemented correctly. The simulated numerical curves were consistent to the results of theoretical calculations, indicating that the model incorporated into GBM-DEM could simulate more realistically similar to the micro-cracking mechanisms. Finally, CCM was used to simulate the uniaxial and biaxial compression tests under the Universal Distinct Element Code (UDEC). The results of the models were in a good agreement with the relevant responses of the rock under different loading conditions, verifying the applicability of the CCM.